Alternative or disruptive family models? Grand/motherhood and posthumous surrogacy in the case of Ana Obregón - Mathilde Cassou (Revista de Bioética y Derecho)
The neoliberalisation and marketisation of fertility have had – and continue to have – tremendous impact on conceptualizations and affordances of kinship. Through the case of Ana Obregón, which caused great controversy in 2023 in Spain, this project examines how ART components such as transnational surrogacy, sperm donation and posthumous reproduction are not only responding to, but also changing, the ways in which family-making is perceived and practised. Following the steps of feminist contributions to the field, this lens interrogates how kinship, a traditional anthropological theme and key social system, is reinserted in new contexts where ARTs predominate. To answer these questions, I explore the public perceptions of this case conveyed in both the press and social media in order to understand how narratives surrounding kinship, surrogacy, posthumous reproduction, and grand/motherhood are constructed and carried out. From a narrative research conceptual framework, a digital ethnography seeks to demonstrate how this case interrogates common sense and exemplifies an alternative family-building strategy which also becomes disruptive as it is inserted into new possibilities allowed by global third-party reproduction. This project also seeks to engage with the existing literature at the intersection of ARTs and kinship to offer a different avenue beyond the classic Anglo-American bibliography. Looking at how women’s bodies shift from private to public sphere when and where childbearing is involved, I explore how subjectivities and asymmetries are conveyed in the public discourse, thus highlighting the power of a single case study to reflect normative attitudes and sociocultural debates.